Amy Margolies, Economic Evaluation of an Early Childhood Development Center-Based Agriculture and Nutrition Intervention in Malawi - Margolies, Amy (2019)
Amy Margolies POLICY SEMINAR Using Malawi’s Community-Based Childcare Centers to Implement an Agriculture and Nutrition Intervention Co-organized by IFPRI, the University of Washington led SEEMS nutrition project, and the CGIAR Research Program on Agriculture for Improved Nutrition and Health (A4NH)